Loanwords in the catechism of M. Petkevičius (1598): slavisms of unknown origin - Smetonienė, Anželika (Lietuvių kalba, 2017)
There are only few studies on lexis of catechism of M. Petkevičius (PK) (1598), even if this is the second book in Lithuanian language in the Grand Duchy of Lithuania and the first hymnal in the Grand Duchy of Lithuania. J. Kruopas concluded vocabulary of this catechism and noted it's loanwords, however, an origin of these words has not been explained. Also, there is no list of equivalents of these borrowed words in Slavic languages, because aim of J. Kruopa's work wasn't to determinate origin of loanwords. The object of this article is Slavic loanwords in the PK, the aim – to specify and to list Slavisms of unknown origin and their equivalents in the Slavic languages. To achieve the aim the following objectives were set: to collect all borrowed words and Slavic stem words from the selected text; to determinate criteria, that can indicate origin of Slavisms, and to classify Slavisms depending on their origin. In total separate 410 Slavic stem lexemes were found in the catechism of M. Petkevičius. After all these lexemes were generalized (e. g. only forms without prefixes are presented), 344 words left: 30 revealed itself to be hybrids, 149 – Slavisms of unknown origin. It only confirms once again that sometimes it is not possible to determine the path of Slavisms into Lithuanian language due to the similarity of the Slavic languages, and therefore it is possible only to give chronologically accurate equivalents of the loanwords of the PK in the Old Russian, Ruthenian and Polish languages.
Keywords: Slavisms; loanwords; origin; Petkevičius; catechism